Importance of oral phase in in vitro starch digestibility related to wholegrain versus refined pastas and mastication impairment. (March 2021) - Blanquet-Diot, S.; François, O.; Denis, S.; Hennequin, M.; Peyron, M.A.
Abstract: Starch represents the main source of carbohydrates in human diet and its digestibility is suspected to be involved in the control of glycemic response. The low glycemic index caused by pastas is mainly attributed to the starch-protein network constituting their compact structure. A significant part of the physico-chemical digestive process probably occurs during mastication with exposure to amylase. However, the respective accountability of oral and intestinal phases in digestion is not clearly established, and this knowledge would especially benefit to health management of people suffering of impaired mastication. Food boluses were produced for in vitro gastrointestinal digestion either by in vitro normal (NM) or deficient mastication (DM) of wholegrain and refined pastas. Boluses were first characterized for physical properties. Many large particles were obtained in DM boluses whatever the pastas. Starch and hydrolysis products were then determined in boluses and gastrointestinal digestas. The beginning of starch hydrolysis was confirmed in the mouth with a production of maltose in the NM boluses, around 1.6 g/100g of cooked pastas, significantly decreased to 1.2 g/100g in the DM boluses, whatever the pastas. Even if the negative effect of DM on gastrointestinal starch hydrolysis into glucose was observed for both pastas, the greatest impact occurred in refined ones with 55.9 ± 0.82 g glucose/100g pastas after NM versus 53.00 ± 0.95 g/100g after DM. This study highlighted the importance to consider the oral phase in digestion studies, regarding the impact of food structure and oral disruption, and especially in case of DM. Graphical abstract: Image 1 Highlights: Wholegrain pastas are normally more fragmented than refined ones at swallowing time. Maltose produced in boluses reflects starch hydrolysis during mastication. Oral digestibility of starch decreases in deficient mastication. Intestinal starch digestibility is lower for whole-grain pasta normally masticated. Intestinal starch digestibility decreases in deficient mastication for both pasta.